REPEAT BREEDING AND ITS TREATMENT IN DAIRY CATTLE OF HIMACHAL PRADESH (INDIA) - A REVIEW - SINGH, M; SHARMA, A; SHARMA, A; KUMAR, P (The Indian Journal of Animal Reproduction, 2022)
Repeat breeding is a major reproductive disorder in dairy cattle and its incidence varies among different management systems, environments and regions. The culling rate of repeat breeder dairy cattle can be reduced by improving their conception rate through careful handling of genitalia during insemination to avoid acquired abnormalities, appropriate treatment of uterine infections, administering hormone therapy to improve fertilization success and lower embryonic mortality, and ensuring insemination of dairy cattle after proper clinical examination by a skilled inseminator.
Keywords: Cattle; Dairy; Etiology; Repeat breeder; Treatment